2020
DOI: 10.3390/cancers12071797
|View full text |Cite
|
Sign up to set email alerts
|

Loss of HMGCS2 Enhances Lipogenesis and Attenuates the Protective Effect of the Ketogenic Diet in Liver Cancer

Abstract: Hepatocellular carcinoma (HCC) is the most common primary malignant liver tumor with limited treatment. The ketogenic diet (KD) emerged as a metabolic therapy for cancer; however, the antitumor effect on HCC remains controversial. We previously reported that the ketogenesis rate-limiting enzyme, 3-hydroxymethylglutaryl-CoA synthase 2 (HMGCS2), was downregulated in most patients with HCC. The knockdown of HMGCS2 enhanced the proliferation and metastasis ability of HCC cells. However, the role of HMGCS2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
0
13
0
3
Order By: Relevance
“…In liver cancer, it is reported that use of a ketogenic diet diminished diethylnitrosamine-induced liver tumor in mice [ 29 ]. Previously, we also reported that a ketogenic diet significantly inhibited liver cancer cell growth in NOD/SCID mice [ 12 , 13 ]. Since the influence of the ketogenic diet on liver fibrosis is still unknown, crucial evidence is needed to evaluate the possibility of developing dietary interventions in liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In liver cancer, it is reported that use of a ketogenic diet diminished diethylnitrosamine-induced liver tumor in mice [ 29 ]. Previously, we also reported that a ketogenic diet significantly inhibited liver cancer cell growth in NOD/SCID mice [ 12 , 13 ]. Since the influence of the ketogenic diet on liver fibrosis is still unknown, crucial evidence is needed to evaluate the possibility of developing dietary interventions in liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In liver disease, the ketogenic diet ameliorated NAFLD progression by promoting weight loss and decreasing the amount of triglyceride in the liver [ 11 ]. Our lab previously reported that a ketogenic diet significantly inhibited liver cancer cell growth in mice [ 12 , 13 ]. Conversely, it is also reported that the ketogenic diet aggravates neurodegeneration and mitochondrial deterioration in a transgenic mouse model [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…HMGCS2 is localized at 1p12, which encodes a mitochondrial hydroxymethylglutaryl coenzyme A synthase (HMGCS) found mainly in the liver and testicular tissues ( Hu et al, 2017 ). It is the first rate-limiting enzyme in ketone body synthesis and can drive malignancy progression and metastasis by promoting ketone body production and reuse ( Koutnik et al, 2020 ; Wang et al, 2020 ). MMP-7 is a stromal lysin protein, and many studies have shown that MMP-7 plays a significant regulatory role in apoptosis, immunity, cell migration, and angiogenesis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…HMGCS2 may function as a tumor suppressor. Indeed, its knockdown induces the proliferation and metastasis ability of HCC cells by enhancing c-Myc/cyclinD1 and epithelial-to-mesenchymal transition (EMT) signaling and alters lipid metabolism, resulting in increases in fatty acid, triglyceride, and cholesterol syntheses [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%